Emergence of Two Inertial Subranges in Solar Wind Turbulence: Dependence on Heliospheric Distance and Solar Activity - Shiladittya Mondal; Supratik Banerjee; Luca Sorriso-Valvo (The Astrophysical Journal)
The solar wind is highly turbulent, and intermittency effects are observed for fluctuations within the inertial range. By analyzing magnetic field spectra and fourth-order moments, we perform a comparative study of turbulence and intermittency in different types of solar wind, measured during periods of solar minima and a maximum. Using eight fast-solar-wind intervals measured during solar minima between 0.3 and 3.16 au, we find a clear signature of two inertial subranges with f ^−3/2 and f ^−5/3 power laws in the magnetic power spectra. The intermittency, measured through the scaling law of the kurtosis of the magnetic field fluctuations, further confirms the existence of two different power laws separated by a clear break. A systematic study of the evolution of the said subranges as a function of heliospheric distance shows the correlation of the break scale with both the turbulence outer scale and the typical ion scales. During solar maximum, on the contrary, the two subranges are not omnipresent, thus showing more variability in the power spectra and intermittency scaling properties.